Proceedings of the 2021 ACM Symposium on Principles of Distributed Computing 2021
DOI: 10.1145/3465084.3467920
|View full text |Cite
|
Sign up to set email alerts
|

Tight Trade-off in Contention Resolution without Collision Detection

Abstract: In this paper, we consider contention resolution on a multiple-access communication channel. In this problem, a set of nodes arrive over time, each with a message it intends to send. In each time slot, each node may attempt to broadcast its message or remain idle. If a single node broadcasts in a slot, the message is received by all nodes; otherwise, if multiple nodes broadcast simultaneously, a collision occurs and none succeeds. If collision detection is available, nodes can differentiate collision and silen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…More recently, Bender et al [6] have shown that in the full-sensing model without collision detection (where processors listen to the channel to learn on which steps there are successful sends but are unable to distinguish between silence and collisions) there is a full-sensing protocol which achieves constant throughput even when the message arrival is adversarial rather than random. Chen et al [7] demonstrate a full-sensing protocol that can achieve a decent throughput, even in the presence of jamming. Despite these advances regarding full-sensing protocols, and other protocols assuming more capabilities from processors than acknowledgement-based protocols [23,13], for acknowledgement-based protocols and even for backoff protocols, the most fundamental possible question remains open: do stable protocols exist at all?…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Bender et al [6] have shown that in the full-sensing model without collision detection (where processors listen to the channel to learn on which steps there are successful sends but are unable to distinguish between silence and collisions) there is a full-sensing protocol which achieves constant throughput even when the message arrival is adversarial rather than random. Chen et al [7] demonstrate a full-sensing protocol that can achieve a decent throughput, even in the presence of jamming. Despite these advances regarding full-sensing protocols, and other protocols assuming more capabilities from processors than acknowledgement-based protocols [23,13], for acknowledgement-based protocols and even for backoff protocols, the most fundamental possible question remains open: do stable protocols exist at all?…”
Section: Introductionmentioning
confidence: 99%
“…With binary exponential backoff, if devices begin the protocol at the same time, it takes Θ( log ) time for all the packets to complete, and the throughput achieved is 1/log [16]. Recent work has shown how to achieve Θ(1) throughput even in an adversarial setting [20,27,28], and Chang, Jin, and Pettie [27] showed how to achieve throughput 1/ − ( ), for any > 0.…”
Section: Introductionmentioning
confidence: 99%
“…With binary exponential backoff, if 𝑛 devices begin the protocol at the same time, it takes Θ(𝑛 log 𝑛) time for all the packets to complete, and the throughput achieved is 1/log 𝑛 [16]. Recent work has shown how to achieve Θ(1) throughput even in an adversarial setting [20,27,28], and Chang, Jun, and Pettie [27] showed how to achieve throughput 1/𝑒 − 𝑂 (𝜀), for any 𝜀 > 0.…”
Section: Introductionmentioning
confidence: 99%
“…Backoff has been studied in a wide variety of different models. Many of the above papers have assumed that radios can detect collisions; some work has focused on the case where there is no collision detection [21,28,36,37]. The large majority of these protocols have been randomized, but there has been some consideration of deterministic protocols [37,73,75,77].…”
Section: Introductionmentioning
confidence: 99%